1999
DOI: 10.1023/a:1024724425597
|View full text |Cite
|
Sign up to set email alerts
|

PTSD among bereaved parents following the violent deaths of their 12‐ to 28‐year‐old children: A longitudinal prospective analysis

Abstract: This study examined the prevalence of posttraumatic stress disorder (PTSD) among parents bereaved by the violent deaths of their 12- to 28-year-old children. A community-based sample of 171 bereaved mothers and 90 fathers was recruited by a review of Medical Examiner records and followed for 2 years. Four important findings emerged: Both parents' gender and children's causes of death significantly affected the prevalence of PTSD symptoms. Twice as many mothers and fathers whose children were murdered met PTSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 37 publications
7
92
2
2
Order By: Relevance
“…Research studies have found that bereaved parents are more likely to experience high rates of grief and mental distress following the death of their child (Dyregrov et al, 2003;Kreicbergs et al, 2004;Murphy et al, 1999). In this study the strong association between spiritual coping strategies and lower levels of grief and mental health symptoms suggests that spiritual coping is a strong positive mediator in the reduction of grief and mental health symptoms for bereaved parents.…”
Section: Discussion Of Findingsmentioning
confidence: 48%
See 3 more Smart Citations
“…Research studies have found that bereaved parents are more likely to experience high rates of grief and mental distress following the death of their child (Dyregrov et al, 2003;Kreicbergs et al, 2004;Murphy et al, 1999). In this study the strong association between spiritual coping strategies and lower levels of grief and mental health symptoms suggests that spiritual coping is a strong positive mediator in the reduction of grief and mental health symptoms for bereaved parents.…”
Section: Discussion Of Findingsmentioning
confidence: 48%
“…Bereaved parents were identified from death certificates but place of death was not reported. Murphy et al (1999) found 40% of bereaved mothers and 14% of bereaved fathers exhibited symptoms of PTSD 4 months after their child's death, however at 24 months bereaved mothers became less symptomatic for PTSD (21%) but the 14% of bereaved fathers remained symptomatic for PTSD. Cause of death also affected the manifestation of PTSD symptoms.…”
Section: Grief In Bereaved Parentsmentioning
confidence: 94%
See 2 more Smart Citations
“…Multiple studies found posttraumatic stress symptoms to be present in grieving parents after a sudden and traumatic death of their child (Kivimäki et al, 2002;Murphy et al, 1999), and parents who lost a child due to suicide developed more symptoms of PostTraumatic Stress Disorder PTSD (Dyregrov et al, 2003). The prevalence of PTSD was found to be present for as long as 5 years in bereaved parents (Murphy, Chung, & Johnson, 2002).…”
Section: Statement Of the Problem Parental Griefmentioning
confidence: 99%